Archaeology under a microscope: research at the ArchaeoMicroLab of the Faculty of Archaeology Adam Mickiewicz University in Poznań - Kurzawska, Aldona; Sobkowiak-Tabaka, Iwona (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
This article presents the newly established ArchaeoMicroLab – the Laboratory of Microscopic Analysis in Archaeology – in the Faculty of Archaeology at Adam Mickiewicz University, its equipment, and the scope of research carried out in this facility. Microscopic analyses are essential research tools used in archaeology for examining artefacts and traces of their use, organic remains, pigments, and many other objects. The use of high magnification enables researchers to capture interesting details that are not visible at the macroscopic level. The article discusses different categories of artefacts, samples and the possibilities of their examination in the laboratory.
Keywords: Microscopic analyses; Microwear analysis / Traceology; Organic residues; Pottery; Stone Tools